The Use of Whatsapp Social Media as Reinforcement Online Learning during the COVID-19 Pandemic - Ramdhani, Taufik; Nandiyanto, Asep Bayu Dani (Universitas Pendidikan Indonesia (UPI), 2021)
Learning is done by humans for life with a specific purpose. Learning is done so the creation of teaching and learning activities. In current conditions, after COVID-19 entered Indonesia, it requires everyone to keep their distance in order to break the chain of spreading the virus. The world of education is also carried out online or remotely so that teaching and learning activities can be carried out. In accordance with the demands of the industrial revolution 4.0, educators must be able to create creative learning in order to create effective learning activities. With that, learning is carried out through online learning media with the use of applications in particular such as the Whatsapp application to strengthen online learning during the COVID-19 pandemic.